Taxonomic status and leaf epidermal features of Amomum Roxb. (Family Zingiberaceae) recorded from Mindanao, Philippines - Acma, Florfe M.; Gruezo, William Sm. (2011)
The taxonomic evaluation of some Amomum species (Family Zingiberaceae) reported from Mindanao Philippines was conducted using both field and herbarium studies supplemented with leaf epidermal characters. Botanical field studies were conducted and specimens were identified using taxonomic keys, protologues and by doing herbarium studies at the Philippine National Museum (PNH), College of Agriculture, University of the Philippines, College, Laguna (CAHUP)and Herbarium of the Singapore Botanical Gardens (SING). Results showed that a member of species originally placed under the genus Amomum are currently classified under the genera as Etlingera giseke [E. dalican (Elm.) Poulsen, E. philippinensis (Ridl.) R.M. Smith] Geocharis [G. fusiformis (Ridl.) R.M. Sm.] and Hornstedtia Retzius [H. conoidea Ridl.] Examination of the leaf epidermal features revelaed that both the Amomum and Geocharis have broad subsidiary cells. Amomum have more stomata located near the veins than halfway between veins. In contrast, the stomata for Hornstedtia and Etlingera are scattered between parallel veins of the leaf. The leaf epidermal data support the current placement of the above-listed formerly considered species of Amomum. Finally, this study showed that previous taxonomic treatment for the Philippine Amomum is quite unsatisfactory.
Keywords: Zingiberaceae; Stomata